2002
DOI: 10.1090/s0894-0347-02-00393-4
|View full text |Cite
|
Sign up to set email alerts
|

Finite quotients of the multiplicative group of a finite dimensional division algebra are solvable

Abstract: We prove that finite quotients of the multiplicative group of a finite dimensional division algebra are solvable. Let D D be a finite dimensional division algebra having center K K , and let N ⊆ D × N\subseteq D^{\times } be a normal subgroup of finite index. Suppose D × / N D^{\times }/N is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…However, in [11], it is shown that, for all positive integers d, there exists a finite special 2-group G such that the commuting graph of G has diameter greater than d. But in [17], it is proved that for finite groups with trivial center the conjecture made in [14] holds good. The concept of commuting graphs of groups (taking, as the vertices, the non-trivial elements of the group in place of non-central elements) has also been recently used in [20] to show that finite quotients of the multiplicative group of a finite dimensional division algebra are solvable. There is also a ring theoretic version of commuting graphs (see, for example, [2], [3]).…”
Section: Introductionmentioning
confidence: 99%
“…However, in [11], it is shown that, for all positive integers d, there exists a finite special 2-group G such that the commuting graph of G has diameter greater than d. But in [17], it is proved that for finite groups with trivial center the conjecture made in [14] holds good. The concept of commuting graphs of groups (taking, as the vertices, the non-trivial elements of the group in place of non-central elements) has also been recently used in [20] to show that finite quotients of the multiplicative group of a finite dimensional division algebra are solvable. There is also a ring theoretic version of commuting graphs (see, for example, [2], [3]).…”
Section: Introductionmentioning
confidence: 99%
“…They were eminent for giving evidence of a prescribed isomorphism of an involution centralizer, where there is a limited number of non-abelian groups capable of containing it. These graphs were extremely vital for the works of the Margulis-Platanov conjecture [2], as the graphs mentioned in [1] have X = G\{1} where 1 is the identity element of G). When X is a conjugacy class of involution (conjugacy class X of G means that for any two elements x, y  X there are an element ISSN: 0067-2904 g G such that x g =y, whereas involution means that all elements of X have order 2), then the commuting graph is known as the commuting involution graph.…”
Section: Introductionmentioning
confidence: 99%
“…In effect commuting graphs first appeared in the paper of Brauer and Fowler [14], famous for containing a proof that up to isomorphism only finitely many nonabelian simple groups can have a given centralizer of an involution. The commuting graphs considered in [14] had X ¼ Gnf1g-such graphs have played an important role in recent work related to the Margulis-Platanov conjecture (see [41]). Various kinds of commuting graphs have been deployed in the study of finite groups, particularly the non-abelian simple groups.…”
Section: Introductionmentioning
confidence: 99%